2020
DOI: 10.1503/cmaj.200791
|View full text |Cite
|
Sign up to set email alerts
|

Confronting the COVID-19 surgery crisis: time for transformational change

Abstract: KEY POINTS• The coronavirus disease 2019 (COVID-19) pandemic has profoundly reduced the capacity of health systems to provide scheduled services such as elective surgery and other nonemergency procedures.• The combination of single-entry models and team-based care is an efficient, fair and ethical approach to addressing the pent-up demand for surgery in the presence of constrained resources.• Even beyond the COVID-19 pandemic, single-entry models and team-based care are effective strategies to reduce wait time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 12 publications
0
57
0
4
Order By: Relevance
“…To effectively manage this impact on more than 140 000 patients, health systems and surgical leaders cannot get back to business as usual, but rather must employ innovative system-based solutions to provide patients with timely surgical care and prepare for future COVID-19 waves. [31][32][33]…”
Section: Resultsmentioning
confidence: 99%
“…To effectively manage this impact on more than 140 000 patients, health systems and surgical leaders cannot get back to business as usual, but rather must employ innovative system-based solutions to provide patients with timely surgical care and prepare for future COVID-19 waves. [31][32][33]…”
Section: Resultsmentioning
confidence: 99%
“…One in 8 women are expected to develop breast cancer during their lifetime, and one in 34 are expected to die of this disease as it is the number one cancer affecting women [ 2 ]. The Coronavirus Disease 2019 (COVID-19) pandemic has placed many strains on the Canadian health care system, in particular to the flow of operating rooms [ 3 ], a resource needed to treat breast cancer. Mitigation strategies for treatment of breast cancer were quickly developed to help deliver appropriate care during the pandemic [ 4 – 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In British Columbia the operating room (OR) slow down started on March 16, 2020 and continued until May 4, 2020 allowing only urgent procedures, including oncology to proceed. Urbach and Martin describe that in Ontario, 45,000 fewer surgeries were performed in adults with non-cancer-related disease in March and April of 2020 (a more than 90% reduction compared to the same time period in 2019) [ 3 ]. They go on to suggest that single entry models and team-based care may be an effective way to reduce pandemic induced prolonged wait times [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The systematic review for SEM also showed a consistently positive impact on access-related variables for referral of patients to surgical clinics (51). Recently, the combination of SEM and team-based care has been recommended as one way to confront the COVID-19 surgery crisis for e cient, fair, and ethical approaches in surgical care pathways (52). However, although this review has found promising results in regard to balancing the variation of total waiting time with SEM, it can be di cult to implement SEM into a referral system due to inadequate stakeholder readiness and participation (42).…”
Section: Discussionmentioning
confidence: 98%